Remoção da amônia por air stripping em canais corrugados helicoidais - Delduque, Thalita Pereira (2017)
The present work intent to verify the performance of a helical corrugated channel applied in the ammonia removal, through the air stripping process.The syst h s i t r l i t r 4 "(≈100 mm) and 10m long, helically arranged. The influence of the operating conditions was evaluated as: air flow (1000 Lmin-1 at 3000 L min-1), liquid flow (0.2 L min-1 at 1.0 L min-1), nitrogen concentration, pH (9.0 to 12.0) and channel slope (5% to 20%) in the ammonia removal. It was performed hydrodynamic characterization of the system with adjustment of the uni-parametric models: complete mix N-reactors in series, big intensity and small intensity dispersal, aiming the determination of the global coefficients of mass transfer (KLa). Among the main results, the alkaline mass required to raise the pH from 5 to 11.5 on average was 2.875 g of NaOH per g of N present in the wastewater. Subsequently, hydrodynamic tests indicated that the drain of the system tends to be pistoned due to its high number of compete mix reactors in grade (49 to 69). A total of 30 experiments were performed using the statistic design, Design Central Composit Rotational (DCCR) with mass transfer coefficient (KLa) of 19.7h-1 under optimized conditions of pH 10.5, Qar=2000 L min-1, Qliq=0.2 L min-1 in the concentration of 0.6 mgL-1 N-NH3 achieving the efficiency of removal of N-NH3 of 70%. With the experimental values it was possible to obtain the reparametrized model of the coded variables, which represents the removal of N-NH3 (%) as a function of pH, air flow, liquid flow and N-NH3 concentration. When compared to conventional air stripping towers, the corrugated channel provided longer air-to-liquid contact time for air injection and lower manometric height of wastewater elevation, reducing constructive and electricity expenditures.